TEKNIK PENILAIAN PROYEK DALAM PEMBELAJARAN BIOLOGI DI MADRASAH ALIYAH - zanuar, Achmad (Balai Diklat Keagamaan Surabaya, 2017)
The project assessment techni que is one of the assessment techniques used to assess skills aspects of the 2013 Curriculum. The use of project assessment techniques is inseparable from the application of project-based learning models. This technique is believed to be able to assess the ability of learners in conducting investigations by making the report of the investigation as the object of hi s assessment. Project assessment has several advantages mainly related to the development of critical thinking skills of learners as they have to carry out a series of investigative activities. The process of implementing a project assessment technique involves two steps. The first step is more on preparing the learners’ work. The following steps are carried out at the time of project assignment unti l impl ementation of the assessment. Assessment of the project task report can be done using the rubric of assessment either in the form of analytic or holistic. A review of the basic competencies of Biology subjects at the Madrasah Aliyah level indicates some basic competencies that should be assessed by project assessment techniques.